Extending the Network Robustness Index to include emissions: a holistic framework for link criticality analysis for Montreal transportation system. Issue 6 (2nd November 2018) - Reynaud, Frederic; Sider, Timothy; Hatzopoulou, Marianne; Eluru, Naveen
ABSTRACT: The Network Robustness Index (NRI) was one of the first tools to successfully assess networkwide congestion effects due to single-link closures. This paper investigates the use of systemwide metrics in the context of Montreal's urban road network, and provides a new mechanism to evaluate the importance of individual links while internalizing the environmental perspective. Specifically, the NRI is expanded to include road emissions in the link criticality analysis process, resulting in the creation of an Emissions-based NRI (ENRI), to be used in conjunction with the NRI. The results of this new Emissions-based NRI (ENRI) are compared with the NRI results and we observe that both tools provide similar results for major scenarios (such as capacity reduction on major bridges) while for minor scenarios (such as capacity reduction on arterial roads) the results are quite different. The results suggest that new holistic frameworks are needed to assess link criticality in urban areas.